Reuse and recovery of products in the reverse logistics process in the omnichannel model on the example of a sports store chain - Skurpel, Dagmara; Bakalarczyk, Bartłomiej Tomasz (Serbian Journal of Management, 2023)
The role of reverse logistics is to ensure that the return of goods is efficient and trouble-free. It is also responsible for determining whether the goods are fully valuable and can be sold again, or whether they should be subjected to additional processes for repair or disposal. The aim of the work is to present the processes of reverse logistics and after-sales customer service based on the Decathlon store chain. The article characterizes several activities that enable recovery of the economic value of used or broken products, such as: repair, renovation, cannibalization or recycling.Depending on the technical condition and the reason for returning the goods to the seller, the returned products will undergo different processes. Goods of full value that have been returned due to the change in the consumer's mind can immediately be returned for resale and issued to another customer. In the event that the goods show signs of use or have been returned for a specific reason given by the customer, it is necessary to check whether the article is suitable for resale. For example the defect can be removed and such a product after service can be returned to warehouse stock. With such items in mind, the 2nd Life department has been created, which takes items with minor damage and reissues them for sale at a discounted price, that meet safety standards or their disposal. Actions that the company takes to reduce waste and ways that the consumer has the opportunity to solve the problem with a defect on their own have been presented.
Keywords: reverse logistic; omnichannel; customer service process; recovery of products